2011
DOI: 10.1074/mcp.m110.002386
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Proteomes and Interactomes Using Parallel Affinity Capture (iPAC) Coupled to Mass Spectrometry

Abstract: Affinity purification coupled to mass spectrometry provides a reliable method for identifying proteins and their binding partners. In this study we have used Drosophila melanogaster proteins triple tagged with Flag, Strep II, and Yellow fluorescent protein in vivo within affinity pull-down experiments and isolated these proteins in their native complexes from embryos. We describe a pipeline for determining interactomes by Parallel Affinity Capture (iPAC) and show its use by identifying partners of several prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 29 publications
0
89
0
Order By: Relevance
“…8). We used a gene trap that generates a YFPNotch fusion protein that is functional and contain the YFP in the extra-cellular domain (Rees et al, 2011). The combination with an antibody directed against NICD revealed that the enlarged endosomes are positive for NECD and NICD and therefore probably contain the full-length receptor and also Dl (Fig.…”
Section: Loss Of Lgd Function In the Follicle Epithelium Results In Amentioning
confidence: 99%
“…8). We used a gene trap that generates a YFPNotch fusion protein that is functional and contain the YFP in the extra-cellular domain (Rees et al, 2011). The combination with an antibody directed against NICD revealed that the enlarged endosomes are positive for NECD and NICD and therefore probably contain the full-length receptor and also Dl (Fig.…”
Section: Loss Of Lgd Function In the Follicle Epithelium Results In Amentioning
confidence: 99%
“…1) 14 . We focused on IR25a, a member of a divergent subfamily of ionotropic glutamate receptors and verified the interaction by co-immunoprecipitation after overexpressing IR25a and NOCTE in all clock cells using tim-gal4 (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Co-immunoprecipitation experiments were performed as described 14 . For each protein purification, 200-300 mg wet-weight of heads from gmr-gal4 flies expressing UAS-nocte-flag (FSNS and FSNH transgenics were used in 2 independent experiments) or gmr-gal4 alone (negative controls) were collected on dry ice and manually homogenized with a 2 ml Dounce homogenizer (Fisher) in 1 ml of extraction buffer (final protein concentration 5mg/ml extraction buffer) containing 50 mM Tris, pH 7.5, 125 mM NaCl, 1.5 mM MgCl2, 1mM EDTA, 5% Glycerol, 0.4% NP-40, and 0.1% Tween 20.…”
Section: Co-immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The following fly strains were used: repo-GAL4 (Sepp et al, 2001); spg-GAL4 (Schwabe et al, 2005); UAS-mCD8::GFP (Lee and Luo, 1999); UAS-mCD8::RFP (a gift from Dr Elizabeth Gavis, Princeton University); UAS-Dicer2 (Dietzl et al, 2007); mys 1 (Bunch et al, 1992); FRT19A,tubP-GAL80,hsFLP,w* ( Lee and Luo, 1999); repo-FLP (Stork et al, 2008); Gli-lacZ (Auld et al, 1995); Perlecan::GFP; NrxIV::GFP; ILK::GFP; αPS1::YFP and αPS2::YFP (Rees et al, 2011); talin::GFP (a gift from Dr Guy Tanentzapf, University of British Columbia). The UAS-RNAi strains used were: UAS-βPS-RNAi(GD) (GD15002), UAS-talin-RNAi(GD) (GD12050), UAS-αPS2-RNAi(GD) (GD44885), UAS-αPS3-RNAi(GD) (GD4891), UAS-NrxIV-RNAi(GD) (GD2436) (Dietzl et al, 2007); UAS-βPS-RNAi(R1) (1560R-1), UAS-αPS2-RNAi(R1) (9623R-2), UAS-αPS3-RNAi(R1) (8095R-1) and UAS-talin-RNAi(R1) (6831R-1) from the National Institute of Genetics, Japan.…”
Section: Fly Strains and Geneticsmentioning
confidence: 99%